Insurance payments in case of the death of the insured person as a result of an accident at work or occupational disease - Burka, Aliona (Visegrad journal on human rights, 2019)
В статье исследуются основания и порядок осуществления страховых выплат в случае смерти потерпевшего в результате несчастного случая на производстве или профессионального заболевания, таких как ежемесячные страховые выплаты и единовременное пособие. Определен круг лиц, имеющих право на страховые выплаты, и рассмотрены отдельные судебные решения по делам о предоставлении ежемесячных страховых выплат и единовременных пособий. Автор статьи прихо- дит к выводу, что правовое регулирование осуществления исследуемых страховых выплат имеет ряд недостатков и требует внесения соответствующих изменений и дополнений в действующее законодательство./ The article examines the grounds and procedure for the implementation of insurance payments in the event of death of the injured person as a result of an industrial accident or occupational disease, such as monthly insurance payments and lump-sum assistance. The circle of persons who have the right to the insurance payments is determined and individual court decisions on granting of monthly insurance payments and one-time assistance are considered. The author of the article concludes that the legal regulation of the implementation of the investigated insurance payments has a number of shortcomings and requires the introduction of appropriate amendments and additions to the current legislation.
Keywords: несчастный случай на производстве; профессиональное заболевание; страховые выплаты; ежемесячные страховые выплаты; единовременное пособие в случае смерти потерпевшего; occupational accident; occupational disease; insurance payments; monthly insurance payments; one-time assistance in the event of death of the injured person